2017
DOI: 10.3748/wjg.v23.i43.7666
|View full text |Cite
|
Sign up to set email alerts
|

Pathological process of liver sinusoidal endothelial cells in liver diseases

Abstract: Cirrhosis develops from liver fibrosis and is the severe pathological stage of all chronic liver injury. Cirrhosis caused by hepatitis B virus and hepatitis C virus infection is especially common. Liver fibrosis and cirrhosis involve excess production of extracellular matrix, which is closely related to liver sinusoidal endothelial cells (LSECs). Damaged LSECs can synthesize transforming growth factor-beta and platelet-derived growth factor, which activate hepatic stellate cells and facilitate the synthesis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 71 publications
2
60
0
1
Order By: Relevance
“…In 2002, Loeffler et al 43 investigated the effect of exposure of human umbilical vein endothelial cells (HUVECs) to Schistosoma mansoni soluble egg antigen (SEA). They documented a marked increase in the HUVEC tube formation, and cell proliferation with a significant reduction of the apoptotic rate 44 …”
Section: Discussionmentioning
confidence: 98%
“…In 2002, Loeffler et al 43 investigated the effect of exposure of human umbilical vein endothelial cells (HUVECs) to Schistosoma mansoni soluble egg antigen (SEA). They documented a marked increase in the HUVEC tube formation, and cell proliferation with a significant reduction of the apoptotic rate 44 …”
Section: Discussionmentioning
confidence: 98%
“…LSECs characteristically possess open fenestrae and unique in comparison to other endothelial cells, they lack an underlying basement membrane. These open fenestrae are 50-150 nm wide pores, which cluster together to act as a two-way channel for the flow of soluble molecules through the endothelial barrier between the blood and hepatocytes [38]. LSECs are also highly efficient scavengers, capable of clearing macromolecules, such as stabilin bound oxidized low density lipoprotein, by endocytic receptor-uptake and trans-cytosis to the Space of Disse, further contributing to the delivery of metabolic substrates from the blood to hepatocytes [39,40].…”
Section: Non-parenchymal Liver Cellsmentioning
confidence: 99%
“…Indeed, expression levels of acetyl-coenzyme-A carboxylase 1, a key enzyme in fatty acid metabolism (Barber et al 2005), were shown to decrease in advanced stages of NASH compared to individuals with steatosis (Nagaya et al 2010). Moreover, in the transcriptional levels, liver X receptor (LXR), a nuclear receptor involved with regulation of cholesterol, fatty acid, and glucose metabolism (Kalaany and Mangelsdorf 2006), correlated with intrahepatic inflammation and fibrosis in NAFLD patients (Ahn et al 2014;Ni et al 2017). In line, macrophage-targeted delivery of LXR agonist inside the atherosclerotic plaque reduced atherosclerosis progression (Guo et al 2018), pointing toward a key function of LXR in both NAFLD and atherosclerosis development.…”
Section: Lipo-and Glucotoxicitymentioning
confidence: 99%
“…Lipotoxic responses also affect LSECs, a type of non-parenchymal cell that is specifically involved in maintaining hepatic vascular tone and quiescence of hepatic stellate cells that are responsible for the fibrotic response. Upon treatment with oxidized lipids (Zhang et al 2014) or palmitic acid (Matsumoto et al 2018), LSCEs directly or indirectly triggered the release of reactive oxygen species (ROS) production (Peters et al 2018), which influences mechanisms related to inflammation and fibrosis (Ni et al 2017).…”
Section: Lipo-and Glucotoxicitymentioning
confidence: 99%